THE IDEA OF RELIGIOUS MODERATION IN INDONESIAN NEW ORDER AND THE REFORM ERA - Muhammad Aqil Irham; Idrus Ruslan; Muhammad Candra Syahputra (Himpunan Peminat Ilmu-Ilmu Ushuluddin (HIPIUS), 2021)
Indonesia is neither a religious state nor a secular state though the majority of its population is Moslem. The relations between Islam and the state have once experienced strong tensions until it finally reached a consensus. However, this consensus had historically experienced distortions and complexities among Moslems themselves and between the Moslems and the government (state), during the New Order Era and the Reform Era. This article tries to describe the development of the idea of religious moderation in the New Order and the Reform Era and explore the views of the Moslem elites in relation to religious moderation policies and their implementation during the era of President Soeharto and in the era of open democracy after the fall of the authoritarian New Order regime. This research relies on an in-depth analysis of academic references and literature. The study shows that there are differences in the aspects of thinking and configuration of Moslem actors in relation to the policy and implementation of religious moderation in the two eras. The research showed that the efforts of the majority of religious people in Indonesia in campaigning for religious moderation intellectually, culturally, and politically by any means, models, modifications and different actors according to the context, challenges, and the spirit of the times had never been faded away so it can not be extinguished.